Research methods and information technology applications in movement science and sport psychology - Muhammad Talha, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The primary purpose of this research study is to describe the methods and information technology applications in movement science and sports psychology. This research study depends upon theoretical form, and secondary data in this research paper describe the application of information technology in sport psychology and movement of sciences. For data determination, used EVIEWS software and some general tests included descriptive statistics, correlation coefficient, unit root test analysis, an examination of equality, and histogram & state related to the variables. The research study also defined the application of each variable. The overall result found positive methods and information technology applications in movement science and sports psychology.